Faith, science and understanding - Polkinghorne, J. C., 1930- (London: Yale University Press, 2000)
"In this captivating book, one of the most highly regarded scientists-theologians of our time explores aspects of the interaction of science and theology. John Polkinghorne defends the place of theology in the university and discusses the role of revelation in religion." "The author examines two related concepts in depth. The first is the divine self-limitation involved in creation that leads to an important reappraisal of the traditional claim that God does not act as a cause among causes. The other is the nature of time and God's involvement with it, an issue that Polkinghorne shows can link metascience and theological understandings. In the final section of the book, the author reviews three centuries of the science and theology debate and assesses the work of major contemporary contributors to the discussion: Wolfhart Pannenberg, Thomas Torrance, and Paul Davies. He also considers why the science-theology discussion has for several centuries been a particular preoccupation of the English."--BOOK JACKET.
"Originally published in 2000 ... by Yale University Press"--Title page verso.
Includes bibliographical references and index.
Keywords: Religion and science